A dysphagia model with denervation of the pharyngeal constrictor muscles in guinea pigs: functional evaluation of swallowing - Hashimoto, Keiko; Sugiyama, Yoichiro; Kaneko, Mami; Kinoshita, Shota; Yamamoto, Ryota; Ishida, Tomoya; Umezaki, Toshiro; Hirano, Shigeru (Frontiers in Neurology, 2024)
Swallowing impairment is a crucial issue that can lead to aspiration, pneumonia, and malnutrition. Animal models are useful to reveal pathophysiology and to facilitate development of new treatments for dysphagia caused by many diseases. The present study aimed to develop a new dysphagia model with reduced pharyngeal constriction during pharyngeal swallowing. Thus, using videofluoroscopic assessment of swallowing in guinea pigs, we analyzed the dynamics of pharyngeal swallowing over time with the pharyngeal branches of the vagus nerve (Ph-X) bilaterally or unilaterally transected. We also evaluated the detailed anatomy of the pharyngeal constrictor muscles after the denervation. Videofluoroscopic examination of swallowing showed a significant increase in the pharyngeal area during swallowing after bilateral and unilateral sectioning of the Ph-X. The videofluoroscopy also showed significantly higher pharyngeal transit duration for bilateral and unilateral section groups. The thyropharyngeal muscle on the sectioned side was significantly thinner than that on the intact side. In contrast, the thickness of the cricopharyngeal muscles on the sectioned and intact sides were not significantly different. The mean thickness of the bilateral thyropharyngeal muscles showed a linear correlation to the pharyngeal area and pharyngeal transit duration. Data obtained in this study suggest that denervation of the Ph-X could influence the strength of pharyngeal contraction during pharyngeal swallowing in relation to thickness of the pharyngeal constrictor muscles, resulting in a decrease in bolus speed. This experimental model may provide essential information 1) for the development of treatments for pharyngeal dysphagia and 2) on the mechanisms related to the recovery process, reinnervation, and nerve regeneration following injury and swallowing impairment possibly caused by medullary stroke, neuromuscular disease, or surgical damage from head and neck cancer.